Navigating Hybrid Language Learning Realities: Students' Views on Workload & Time Allocation during Covid-19 - Khatib, Ahmad Jum’a; Riady, Yasir (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2023)
The Covid-19 pandemic in Indonesia led a shift in university learning policies towards a hybrid learning model. The objective of this study is to determine how English literature students feel about the workload and time suitability of hybrid learning. The descriptive quantitative research method was employed, with questionnaires serving as instruments. The questionnaire consisted of five Likert items in order to gather information for the research findings. The questionnaire was distributed to 467 out of 870 students enrolled in the English Literature Study Program at Gunadarma University using google form and was analysed using a descriptive approach. Data collection used random sampling technique in the odd semester of the 2021/2022 academic year. Ali’s (2018) three aspects of learning literature were used to categorize the data. The eight courses perceived were categorised into 3 groups, e.g., language structure (ls), rhetorical (r) and contextual knowledge (ck). The research results show that perceptions related to time suitability are very good with an average of 45.30% (ck), 48.68% (r), and 48.9% (ls). The perception of workload also has positive results, with 41.14% (ls), 42.26% (r) and 48.7% (ck). These results indicate that the learning model is feasible and acceptable for language and literature study program. The findings highlighted collaboration and commitment of participants in hybrid learning environments. It also displayed the eight courses that were thought to be required for determining the best teaching-learning strategy to use for hybrid learning. In order to improve these findings, it is suggested that additional research be conducted to investigate students' perceptions of other variables.